2002
DOI: 10.1046/j.1471-6712.2002.00059.x
|View full text |Cite
|
Sign up to set email alerts
|

Breast cancer and experiences of social support

Abstract: The present study aimed to describe how 10 Norwegian women with newly diagnosed breast cancer experienced living with the disease. A qualitative method based on principles in Grounded Theory was used. Data were collected through in-depth interviews. This paper explores the experience of social support as it evolves in women's relationships with others. Social support contains emotional, practical and informative dimensions. Here relationships are called interactions. Interaction can be divided into two groups.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
28
0
5

Year Published

2008
2008
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 24 publications
4
28
0
5
Order By: Relevance
“…Landmark et al (2002) carried out a study of women with breast cancer and determined that their most important sources of social support were their families and their friends. [25] A similar study found that Iranian cancer patients' perceptions of social support were at high levels, and that their main source of support was family members. [26] The current study also determined that hope level scores of uro-oncology patients were more than moderately high.…”
Section: Resultsmentioning
confidence: 93%
“…Landmark et al (2002) carried out a study of women with breast cancer and determined that their most important sources of social support were their families and their friends. [25] A similar study found that Iranian cancer patients' perceptions of social support were at high levels, and that their main source of support was family members. [26] The current study also determined that hope level scores of uro-oncology patients were more than moderately high.…”
Section: Resultsmentioning
confidence: 93%
“…It is reported that the difficulties experienced in the process may cause patients to become closer to some of their family members and drift apart from some other family members (Çam and Gümüş, 2006;Dedeli et al, 2008). The uncertainty and fear experienced in the process often cause an increase in the need for social support (Rustøen and Begnum, 2000;Landmark et al, 2002;Çam and Gümüş, 2006). It is reported that the social support provided by the family affects the adaptation process and longevity positively (Tan et al, 2005;Fadıloğlı et al, 2006;Yoo et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the participants who work had higher social support and social support friends sub-dimension scores; the relationship was found to be statistically significant. Studies show that women with breast cancer less frequently focus on their illness in their working environment, benefit from the directive effect of the working environment in terms of intellectual meaning, and get the social support they need through the social network in the working environment (friends and organizational connections) (Landmark et al, 2002). It is indicated that the social support provided to cancer patients by their friends yields positive improvements in the course of the disease by affecting patients' general well-being (Arora et al, 2007;Adler et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Toutefois, une attribution causale interne s'avère associée positivement à l'anxiété-trait et à un coping centré sur l'émotion et le problème [11]. Le soutien des proches, quant à lui, est l'appui le plus important [21]. L'aide du mari et le contact avec les amis sont jugés comme une valeur inestimable dans la lutte contre la maladie [21].…”
unclassified
“…Le soutien des proches, quant à lui, est l'appui le plus important [21]. L'aide du mari et le contact avec les amis sont jugés comme une valeur inestimable dans la lutte contre la maladie [21]. Il est significativement associé à une évolution favorable du cancer [10].…”
unclassified